Crisis in theory and literary criticism. A return to the great teachers - Yauri Montero, Marcos (2020)
The crisis that today is affecting to the theory and literary criticism, has encouraged to the growers of these fields the necessity of redirecting their work starting with the creative heritage of the great masters of the twentieth century. This is a movement with a double meaning, by one side they take the capitalist ideas of the great masters, and in the other part this wisdom is the beginning of new strategies to return  the theory and literary criticism to it’s true channels.